BID RIGGING SEBAGAI BENTUK PRAKTEK PERSAINGAN USAHA TIDAK SEHAT - Bobby Wijanarko (Journal of Management and Business, 2005)
"The Law of The Republic Indonesia Number 5 Year 1999 Concerning the Prohibition ofMonopolistics Practices and Unfair Business Competition intended for the enforcement of provisions of law and providing equal protection for every business actor in an effort to create fair business competition. Business actors shall be prohibited from entering into conspiracies with other parties in order to determine awardess of tenders which may result in unfair business competition.Bid rigging is a particular form of collusive pricefixing behaviour by which firms coordinate their bids on procurement or project contract. Bid Rigging is an agreement between parties over which competitor will win a tender -often from government agencies. This agreement may be accomplished by one or more bidders agreeing to refrain from submitting bids, or by the bidders agreeing on a low bidder and then bidding above that firm's intended (and inflated) price. The tendering process is designed to promote fairness and ensure that the lowest possible prices are received".